2018
DOI: 10.1056/nejmoa1710895
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Safety of Febuxostat or Allopurinol in Patients with Gout

Abstract: In patients with gout and major cardiovascular coexisting conditions, febuxostat was noninferior to allopurinol with respect to rates of adverse cardiovascular events. All-cause mortality and cardiovascular mortality were higher with febuxostat than with allopurinol. (Funded by Takeda Development Center Americas; CARES ClinicalTrials.gov number, NCT01101035 .).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
548
3
31

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 685 publications
(589 citation statements)
references
References 20 publications
7
548
3
31
Order By: Relevance
“…Considerable observational data suggest that allopurinol is associated with cardiovascular benefit 10, 19, 20. Yet, febuxostat, a more potent xanthine oxidase inhibitor and hypouricemic agent, has recently been shown in a randomized clinical trial to lead to increased cardiovascular and all‐cause mortality compared with allopurinol 21. The ongoing ALL‐HEART (Allopurinol and Cardiovascular Outcomes in Patients With Ischemic Heart Disease) randomized trial will assess whether patients with ischemic heart disease derive cardiovascular benefit from allopurinol therapy versus standard of care 22…”
Section: Discussionmentioning
confidence: 99%
“…Considerable observational data suggest that allopurinol is associated with cardiovascular benefit 10, 19, 20. Yet, febuxostat, a more potent xanthine oxidase inhibitor and hypouricemic agent, has recently been shown in a randomized clinical trial to lead to increased cardiovascular and all‐cause mortality compared with allopurinol 21. The ongoing ALL‐HEART (Allopurinol and Cardiovascular Outcomes in Patients With Ischemic Heart Disease) randomized trial will assess whether patients with ischemic heart disease derive cardiovascular benefit from allopurinol therapy versus standard of care 22…”
Section: Discussionmentioning
confidence: 99%
“…The preclinical studies of febuxostat have shown no cardiovascular toxic effects. A large number of patients discontinued participation in the trial, and in the intention-to-treat analysis includes merely 10% of patients (White et al, 2018). It is therefore recommended that, within the clinical setting, related risk factors should be monitored for increasing the safety of the drug treatment.…”
Section: Safetymentioning
confidence: 99%
“…Febuxostat is indicated for the chronic management of hyperuricemia in patients with gout, and the most common adverse events in patients taking febuxostat are liver function abnormalities, nausea, arthralgia and rash [24]. Recently, in patients with gout and coexisting cardiovascular disease, patients treated with febuxostat were found to have an increased risk of cardiovascular death compared with those treated with allopurinol [25].Although monotherapy use of XOIs can be efficacious, there are challenges associated with the utilization of XOIs and with patients achieving sUA target. These challenges include inadequate dosing, lack of follow-up monitoring and dose adjustment, as well as poor drug adherence [26].…”
mentioning
confidence: 99%
“…Febuxostat is indicated for the chronic management of hyperuricemia in patients with gout, and the most common adverse events in patients taking febuxostat are liver function abnormalities, nausea, arthralgia and rash [24]. Recently, in patients with gout and coexisting cardiovascular disease, patients treated with febuxostat were found to have an increased risk of cardiovascular death compared with those treated with allopurinol [25].…”
mentioning
confidence: 99%